2010
DOI: 10.1038/ijo.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

Leptin intake during the suckling period improves the metabolic response of adipose tissue to a high-fat diet

Abstract: Background: The intake of leptin during the suckling period protects against obesity and improves insulin and central leptin sensitivity in adult rats. Objective: We analyzed whether leptin treatment to neonates may also improve later peripheral leptin sensitivity in adipose tissue under high-fat (HF) diet conditions. Design: Male rats were supplemented with a daily oral dose of leptin or the vehicle (controls) during the suckling period. After weaning, animals were fed a normal-fat or an HF diet until the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 50 publications
3
49
0
1
Order By: Relevance
“…Interestingly, animals treated with leptin during lactation were programmed for lower body weight, fat content, and took up fewer calories (4,36). Moreover, our study is supported by data of Priego et al (37) who showed that leptin intake during the suckling period of neonatal rats improves the leptin sensitivity and metabolic response later on in life as evaluated by the expression of the leptin receptor (OB-Rb) and genes related with energy intake. Therefore, our results support the hypothesis that leptin during early lactation could have long-term effects on regulating body weight and appetite (15,38).…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, animals treated with leptin during lactation were programmed for lower body weight, fat content, and took up fewer calories (4,36). Moreover, our study is supported by data of Priego et al (37) who showed that leptin intake during the suckling period of neonatal rats improves the leptin sensitivity and metabolic response later on in life as evaluated by the expression of the leptin receptor (OB-Rb) and genes related with energy intake. Therefore, our results support the hypothesis that leptin during early lactation could have long-term effects on regulating body weight and appetite (15,38).…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, CR female animals also showed higher expression levels of CPT1m in the adipose tissue than their controls, although only under NF diet. This suggests that CR female rats may have greater fatty acid oxidation capacity in adipose tissue, which is of great importance for the control of whole body weight and fat reserves, and may be related to the pattern of ObRb expression in this tissue, as previously described [59]. All in all, these results on gene expression may indicate that CR female animals are more sensitive to the peripheral action of leptin, and this agrees with the lower plasma leptin levels and the better response of the circulating hormone to fasting, suggesting that CR females are more resistant to the development of overweight under HF diet conditions than their controls.…”
Section: Discussionsupporting
confidence: 64%
“…Increased insulin sensitivity has also been previously described in the offspring of severe protein and caloric restricted rats during lactation [25,[56][57][58]. Other conditions during the early neonatal period, such as the supplement of suckling rats with physiological doses of leptin has also been associated in male animals with improved insulin sensitivity [8] and with better metabolic adaptations to HF diet feeding [59]; in concrete, changes at the gene expression level in the adipose tissue evidenced a better capacity of leptin-treated animals to handle and partition the excess of fuel under HF diet feeding, preventing other metabolic disorders related with HF diet feeding, such as hepatic lipid accumulation [59].…”
Section: Discussionmentioning
confidence: 82%
“…Leptin, which is naturally present in maternal milk, is known to play a key role during the suckling period [12]. Leptin supplementation (physiological doses) in rats during the suckling period has later effects in the offspring, preventing overweight in adulthood [13] as well as other alterations related with the metabolic syndrome [47], and also improves later insulin and leptin sensitivity [14]. These beneficial effects of leptin during lactation seem to be related, at least in part, with a better control of food intake, associated with epigenetic changes in the promoter methylation of POMC [48].…”
Section: Discussionmentioning
confidence: 99%